Dypsis lutescens, Areca Palm - Melissa H. Friedman; Michael G. Andreu; Mary McKenzie (EDIS)
This document provides an overview of the Areca Palm (Dypsis lutescens), detailing its taxonomy, common names, and physical characteristics. Native to eastern Madagascar, this palm is endangered in its natural habitat but widely cultivated in Florida and the United States. It thrives in well-drained soils with ample water and can grow up to 35 feet tall. The article also discusses its horticultural applications, including its use as a landscape accent and natural fence, and offers care recommendations such as planting during the rainy season and regular fertilization to maintain its green color. Original publication date May 2010.